Presentation: The Power of the Sacred - Iguíñiz Echeverría, Javier (1992)
There are several voices that speak at this time of a crisis of civilization on a planetary scale. In the various countries of the world, the principles that organized the societies and states of the 20th century are being questioned. Being a universal crisis, however, the way it is experienced and perceived differs from one place to another. Thus in the southern hemisphere we are experiencing its most critical aspects.